Energy Security in the Context of Contemporary Geopolitical Challenges - Ruszel, Mariusz; Turowski, Paweł (Roczniki Nauk Społecznych, 2024)
This article examines contemporary energy security within the evolving landscape of geopolitical challenges, focusing on the impact of strategic energy resources and the resilience of energy infrastructure. The study aims to assess energy security through a national framework, emphasizing the role of state mechanisms over market dynamics in ensuring continuous energy supplies. The core hypothesis suggests that geopolitical tensions and global energy trends directly affect energy security levels. Key research questions include understanding the state’s role in securing energy resources, identifying risks from geopolitical instability, and evaluating infrastructure resilience requirements. The analysis shows that modern energy security extends beyond mere continuity of supply, incorporating aspects of cyber protection, adaptive regulatory policies, and technological advancements in renewable energy production. Key findings emphasize the need for states to adopt proactive strategies for energy diversification, infrastructure security, and crisis readiness, particularly in response to the ongoing Russia-Ukraine conflict, which has transformed global energy markets and amplified the EU’s focus on sustainable, independent energy systems.